An Assessment of Dental Anxiety in Patients Before and After Scaling and Polishing Procedures - Sreeja, Sai S.; Bhandary, Rahul; Bhat, Amitha Ramesh; Shenoy, Nina (Journal of Health and Allied Sciences NU, 2021)
Introduction As of now, there are not many investigations about the improvement of dental apprehension and dental participation in various populations over time. This investigation includes an examination of emotional appraisals of levels of dental apprehension in patients selected at the AB Shetty Memorial Institute of Dental Sciences. The investigation also aimed to discover the causes of dental apprehension as well as the effect of sexuality on the distinguished dental apprehension.Materials and Methods The level of dental apprehension was assessed using questionnaires that included 15 questions before and after the scaling and polishing procedures for 78 patients. The typical features were drawn such as gender, age, and oral hygiene habits. The data analysis was analyzed using paired t-test or Wilcoxon signed rank test to assess pre- and postanxiety levels.Results A total of 78 responses were collected, resulting in a participation rate of 100%. Despite the fact that women had significantly higher overall dental apprehension levels compared with men, the discrepancy among the two genders was substantial and could be clarified.Conclusion Dental fear was common in females, especially among those with dental problems, and a larger degree of dental fear can contribute to periodontal disease.
Keywords: dental apprehension; gender difference; oral hygiene